OBSERVATIONS ON THE SEASONAL FLUCTUATIONS OF PLANKTON IN THE CHILKA LAKE - Patnaik, S (Indian Journal of Fisheries, 2011)
This paper gives an account of the main features of the plankton of f-e Chilica Lake from April, 1964 to March, 1965. The seasonal fluctuations of the main constituent groups of phytoplankton and zooplankton in relation to some of Jthe environmental variables have been discussed. The diatoms and copepods formed the dominant groups in the plankton during the above period.